FUGIN hot core survey. I. Survey method and initial results for l = 10°–20°. (6th April 2021) - Sato, Kazuki; Hasegawa, Tetsuo; Umemoto, Tomofumi; Saito, Hiro; Kuno, Nario; Seta, Masumichi; Sakamoto, Seiichi
Abstract: We have developed a method to make a spectral-line-based survey of hot cores, which represent an important stage of high-mass star formation, and applied the method to the data of the FUGIN (FOREST Unbiased Galactic plane Imaging survey with the Nobeyama 45 m telescope) survey. First, we select hot core candidates by searching the FUGIN data for the weak hot core tracer lines (HNCO and CH3 CN) by stacking, and then we conduct follow-up pointed observations on these candidates in C 34 S, SO, OCS, HC3 N, HNCO, CH3 CN, and CH3 OH J = 2–1 and J = 8–7 lines to confirm and characterize them. We applied this method to the l = 10°–20° portion of the FUGIN data and identified 22 "HotCores" (compact sources with more than two significant detections of the hot core tracer lines, i.e., SO, OCS, HC3 N, HNCO, CH3 CN, or CH3 OH J = 8–7 lines) and 14 "DenseClumps" (sources with more than two significant detection of C 34 S, CH3 OH J = 2–1, or the hot core tracer lines). The identified HotCores are found to be associated with signposts of high-mass star formation such as ATLASGAL clumps, WISE H ii regions, and Class II methanol masers. Many of the FUGIN HotCores are identified with the Herschel Hi-GAL clumps with a median mass of 6.8 × 10 2 M ⊙ and a median bolometric luminosity of 7.4 × 10 3 L ⊙ . Five of the seven HotCores with stronger CH3 CN lines exhibit elevated gas temperatures of 50–100 K. These observations suggest that FUGIN HotCores are closely related to the formation of stars with medium to high mass. For those associated with ATLASGAL clumps, their bolometric luminosity to clump mass ratios are consistent with the star formation stages centered at the hot core phase. The catalog of FUGIN HotCores provides a useful starting point for further statistical studies and detailed observations of high-mass star forming regions.